2010
DOI: 10.1016/j.jmu.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Sonography Facilitates the Diagnosis of Adolescent Anterior Superior Iliac Spine Avulsion Fracture

Abstract: KEY WORDSanterior superior iliac spine, avulsion fracture, sonography Anterior superior iliac spine (ASIS) avulsion fractures are not common. We describe a 15-yearold boy who suffered from sudden onset of pain on the left side of his groin when running a race, accompanied by weakness in raising his left leg. Physical examination revealed local tenderness over left ASIS area, initial pelvic radiograph showed no abnormalities, but kidney-ureter-bladder radiograph revealed a small indistinct radiopaque shadow lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Reports of ultrasound use in diagnosing PAFs are scarce. A previous case report from a rehabilitation department showed the utility of ultrasound for detecting an ASIS avulsion fracture in adolescent male although the technique was performed after a pelvic X-ray finding led to suspicion of a fracture [6]. A previous case-series study demonstrated that ultrasound performed by a radiologist was useful in detecting ASIS and AIIS avulsion fractures [7].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of ultrasound use in diagnosing PAFs are scarce. A previous case report from a rehabilitation department showed the utility of ultrasound for detecting an ASIS avulsion fracture in adolescent male although the technique was performed after a pelvic X-ray finding led to suspicion of a fracture [6]. A previous case-series study demonstrated that ultrasound performed by a radiologist was useful in detecting ASIS and AIIS avulsion fractures [7].…”
Section: Discussionmentioning
confidence: 99%